Revision of the Terellia virens Group (Diptera, Tephritidae) with Description of Three New Species - Korneyev, V.A.; Evstigneev, D.A.; Karimpour, Y.; Kutuk, M.; Mohamadzade Namin, S.; Omur Koyuncu, M.; Yaran, M. (Вестник зоологии, 2013)
The Terellia virens group includes eight species of uniformly greenish flies with white setulose abdomens and hyaline wings, variable in the characters of the male and female terminalia. Three new species are described and illustrated: Terellia freidbergi sp. n. from Middle and Near East, from flower heads of Centaurea behen L., T. ivannikovi V. Korneyev et Evstigneev, sp. n. from European Russia, Kazakhstan and Uzbekistan, breeding in flower heads of Ce. chartolepis Greuter, and T. whitei V.?Korneyev et Mohamadzade, sp. n. reared from flower heads of Cousinia spp. in Kazakhstan, Kyrgyzstan, Turkmenistan and Iran. Illustrated diagnoses or redescriptions of other species and a key to the species of Terellia with hyaline wings and white setulose abdominal tergites are given.